Adesmia boronioides and Solidago chilensis, two novels herbal infusions with toxic effects against colon cancer derived cells - Gastaldi, Bruno (2018)
The development and progression of colon cancer is strongly influenced by diet substances that enter in the digestive tract. Herbalinfusions from medicinal plants usually contains phytochemicalsthat can restrain the development and progression of colon cancerin various ways. Flavonoids, an important group of these phytochemicals, report a recognized anti-inflammatory, antioxidant andsignal-regulating properties. Adesmia boronioides and Solidagochilensis are two native medicinal plants that contain flavonoids andhave reported promising antiproliferative activity against T-84 cells.Our aim was to study the toxic effects of herbal infusions obtainedfrom A. boronioides and S. chilensis on Caco-2 and HT-29 cells asmodels of colon cancer.We observed by MTT assay (after 72 h) that the percentage ofviable cells decreased with the increase in the concentration offreeze-dried infusions of both plant species (0 to 50 mg/ml) (p<0.05,n= 3). S. chilensis had a higher antiproliferative effect (EC50 (mg/ml): 0.57±0.06 and 0.18±0.02) in comparison with A. boronioides(EC50 (mg/ml): 1.27±0.08 and 2.87±0.21), for Caco-2 and HT-29cells, respectively. Colchicine was used as positive control. Similarresults were obtained by Trypan blue exclusion technique (p<0.05,n= 3). After staining the cells with AO and Et/Br, apoptosis cells(orange cells) were observed under the fluorescence microscope.The basal apoptotic percentage (24h) was increased in A. boronioides (35.0±4.1 and 46.2±8.2%) and in S. chilensis (47.2±6.7 and35.8±4.0%) with respect to control (3.8±4.9 and 2.7±3.1%) in Caco2 and HT-29, respectively (p<0.05, n=3). The Procaspase-3 expression was also checked.We conclude that the infusion of the both species exert strong antiproliferative activity on cells derived from colon cancer, partly dueto the modulation of basal apoptosis. Its effects show to be muchgreater in comparison with other species studied. These results provide a direction for further researches about the antitumoral potentialof these native plants.